1990
DOI: 10.1128/jvi.64.6.3093-3096.1990
|View full text |Cite
|
Sign up to set email alerts
|

v-mos protein produced by in vitro translation has protein kinase activity

Abstract: The v-mos protein, termed p37v-ms, has a closely associated serine/threonine protein kinase activity. To provide further information about its protein kinase activity, we tested the activity of p37V-"s produced in a cell-free translation system from transcripts generated from a cloned v-mos gene. Anti-mos(37-55) immunoprecipitates of in vitro-produced p37V-?Os were found to possess serine/threonine protein kinase activity, whereas those obtained with anti-mos(260-271), known to block v-mos autophosphorylation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Considering the sensitivity of detection in this type of experiment, we believe that more than 90% of 35 S-labeled p37 v-mos stayed in the hypophosphorylated form after the kinase reaction and was therefore inactive. In a similar experiment, we previously found that most of the v-Mos produced by in vitro translation in rabbit reticulocyte lysate was also inactive (26). Whether a large percentage of v-Mos is also inactive in vivo is a more difficult question.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Considering the sensitivity of detection in this type of experiment, we believe that more than 90% of 35 S-labeled p37 v-mos stayed in the hypophosphorylated form after the kinase reaction and was therefore inactive. In a similar experiment, we previously found that most of the v-Mos produced by in vitro translation in rabbit reticulocyte lysate was also inactive (26). Whether a large percentage of v-Mos is also inactive in vivo is a more difficult question.…”
mentioning
confidence: 71%
“…4B). Significantly, the more slowly migrating species of GST-Mos, which typically result from v-Mos autophosphorylation (26,32), were present in dramatically reduced amounts upon PKA c coincubation. In this experiment, contaminating reticulocyte lysate kinase(s) also caused some phosphorylation of GST-Mos (e.g., Fig.…”
Section: Inhibition Of V-mos Kinase By Pkamentioning
confidence: 95%
“…In mammalian gonad tissues Mos appears to play an important role in maturation of male and female germinal cells [27–29]. However, various other somatic cell lineages and tissues express significant amounts of Mos products [30–32]. Accumulation of Mos during skeletal muscle development suggested a particular function(s) of Mos in this tissue [33].…”
Section: Introductionmentioning
confidence: 99%
“…Prestained molecular mass markers are shown on the left. Exposure time, 10 h. mobility in sodium dodecyl sulfate (SDS)-polyacrylamide gels (10,14). The major v-mos band produced from antimos(37-55) immune complexes derived from chronically Mo-MuSV-infected NIH 3T3 cells corresponds to the hyperphosphorylated species (Fig.…”
mentioning
confidence: 99%
“…4. v-mos proteins were immunoprecipitated with anti-mos(37-55) antibodies, and the autophosphorylation reaction was caried out as described previously (10,29). Lanes 1 and 2, Mo-MuSV v-mos; lanes 3 and 4, MPSV v-mos; lanes 5 and 6, ts159 MPSV v-mos; lanes 7 and 8, no RNA.…”
mentioning
confidence: 99%